Consultório na rua pintando saúde: uma proposta de educação permanente em saúde - Gil, Elisete da Silva (Universidade do Vale do Rio dos Sinos, 2016)
The Street Doctor´s Office (SDO) is a proposal from the Ministry of Health which aims to provide solution to the needs of homeless people. Through the development of full in loco actions, with wide approaches that seek to grant access to health services, social assistance, among other services, the Street Doctor´s Office team (SDOt) performs its activities itinerantly, with actions on street, in special facilities and in mobile units. The objective of this essay was to suggest a Health Permanent Education Program to the “Pintando Saúde” Street Doctor´s Office, of the Conceição Hospital Group, in Porto Alegre/RS. This is a qualitative, descriptive and exploratory study, conducted at Pintando Saúde SDO. The participants were the very professionals of the SDOt that is being studied. The gathering of information was performed in two stages: 1st) field observation, along with the SDO in its approaches and services to the population (on street and health services); 2nd) focal group with the SDOt. There came up two categories of results: Frailties and challenges on daily work at the SDO; Strategies to overcome the work frailties and challenges at the SDO. The Health Permanent Education Program for the workers of the Street Doctor´s Office has been created according to the needs mentioned by the SDOt. Divided in three proposals: Pintando Saúde Studies Group, 1st Pintando Saúde Street Doctor´s Office Forum and Six-monthly Seminar of Presentation of Researches Conducted in 2017. The presented considerations demonstrate strategies to overcome the invisibility of homeless people, important institutional improvements for the team and the doctor´s office articulation with the socio-assistance services network to this population.
Keywords: População em situação de rua; Consultório na rua; Educação permanente em saúde; Homeless people; Street doctor´s office; Health permanent education; ACCNPQ::Ciências da Saúde::Enfermagem